2016
DOI: 10.1002/mus.25216
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution ultrasound in combat‐related peripheral nerve injuries

Abstract: High resolution peripheral nerve US is a useful modality in assessment of combat-related PNI. Muscle Nerve, 2016 Muscle Nerve 54: 1139-1144, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…In their study, ultrasound was superior to electrodiagnostic test in the ability to clearly demonstrate the specific site of focal nerve involvement among four adults post gunshot or blasts injuries with non-excitable nerve responses; the location was later confirmed by surgical inspection. 119…”
Section: Traumatic Nerve Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, ultrasound was superior to electrodiagnostic test in the ability to clearly demonstrate the specific site of focal nerve involvement among four adults post gunshot or blasts injuries with non-excitable nerve responses; the location was later confirmed by surgical inspection. 119…”
Section: Traumatic Nerve Injuriesmentioning
confidence: 99%
“…– 117 Pillen et al 118 recently showed that the cervical roots, brachial plexus, and proximal nerves can be visualized by ultrasound as early as the neonatal period, and reference data are available from their standardized nerve ultrasound protocol. As well, Smith et al 119 reported on the utility of ultrasound for patients with combat-related peripheral nerve injuries, in addition to standard clinical, EMG, and MRI exams. In their study, ultrasound was superior to electrodiagnostic test in the ability to clearly demonstrate the specific site of focal nerve involvement among four adults post gunshot or blasts injuries with non-excitable nerve responses; the location was later confirmed by surgical inspection 119 …”
Section: Practical Uses Of Nerve Ultrasoundmentioning
confidence: 99%
“…B-mode ultrasound provides the advantages of being convenient, rapid, non-invasive, and easily portable. Bedside examination is possible when using ultrasound, which reduces further injury of the patient due to movements [ 25 – 27 ]. The United States military also provides B-mode ultrasound to assist with the diagnosis of tension pneumothorax during battlefield emergency rescue.…”
Section: Injury Assessment and Diagnosis For Early Treatment Institutmentioning
confidence: 99%
“…[8][9][10] It can sometimes make a diagnosis when EMG is not tolerated or non-informative-for example, by helping to localize pathology when all responses are absent. 11,12 This review will focus on the technical and practical aspects of ultrasound as an imaging technique for muscles and nerves. It can be used as a "how-to" guide to get started with neuromuscular ultrasound in daily practice, to implement a diagnostic tool that adult and pediatric neurologists, clinical neurophysiologists and other specialists can use for patient-friendly, point-of-care imaging.…”
mentioning
confidence: 99%